Panoramic radiography features of complex odontoma in impacted teeth: a scoping review - Anastasya Natalia; Azhari Azhari; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: This review article is aimed to determine panoramic radiograph images of complex odontoma images involving impacted teeth. Review: This study is a scoping review consisting of English or Indonesian articles of complex odontoma in impacted teeth and published in 2010 – 2021. The article search databases used were PubMed, Science Direct, EbscoHost, and Clinical Key with the keyword “(((Complex Odontoma) AND Impacted teeth) AND panoramic radiograph).” The selected articles were screened by checking the publication year, duplicating articles, reading the titles and abstracts, and the entire article's contents. The total search results for articles based on keywords obtained were 621 articles, then 11 articles were used. In all articles covered, the number of impacted teeth is 45, dominated by 32 maxillary and mandibular molars. The majority of lesions formed on the maxillary and mandibular posteriors were not associated with other abnormalities. The majority of the lesions affect the growth of the surrounding teeth and extend to the surrounding jawbone. Conclusion: Panoramic radiographs of Complex Odontoma involving impacted tooth in the form of a homogeneous radiopaque lesion with an oval or irregular shape with a lesion density more significant than bone and surrounding tissue. A well-defined radiolucent lesion surrounds this radiopaque lesion in the form of a connective tissue capsule.